Digital finance, e-commerce development, and regional trade development - Zheng, Minyu (Elsevier Ltd, 2025)
This paper constructs an empirical model that includes digital finance, e-commerce development, and regional trade development, and selects 297 prefecture-level cities in China from 2010 to 2023 as samples for analysis. The study finds that the development of digital finance significantly promotes regional trade development. The mediation effect analysis shows that the development of digital finance diversifies the financing channels for e-commerce enterprises, drives the upgrading and transformation of related industries, and promotes regional trade development. The heterogeneity analysis reveals that the development of digital finance significantly promotes trade development in western regions but has no significant impact on eastern and central regions, which may be related to the different levels of financial development in these regions.